WOMEN CEO, CEO TENURE, GREEN ACCOUNTING, DAN FAKTOR LAIN TERHADAP FIRM VALUE - Rinjani, Rinjani; Sanjaya , Laura Agustine (E-Jurnal Akuntansi TSM, 2024)
This study aims to analyze the influence of independent variables, namely women CEO, company size, leverage, sales growth, company age, green accounting, and CEO tenure, on firm value as the dependent variable in manufacturing companies. The study focuses on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The study resulted in a sample of 85 companies with a total of 255 data points. The analysis was conducted using multiple regression with SPSS. The results show that leverage and CEO tenure positively influence firm value, while women CEO, company size, sales growth, company age, and green accounting have no significant effect on firm value.